Meta-type all aromatic polyamide fiber and manufacturing method thereof

By controlling the particle size distribution of the neutralizer and the fiber cross-sectional shape during the polymerization process and optimizing the spinning process parameters, the strength and elongation fluctuation problems of meta-type all-aromatic polyamide fibers are solved, and stable fiber performance is achieved and suitable for protective clothing.

JP2025019362APending Publication Date: 2025-02-07TEIJIN LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023122931
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the breaking strength and elongation of meta-type all-aromatic polyamide fibers have high fluctuations, resulting in unstable tearing strength of fabrics and difficult to meet the needs of industrial production.

Method used

By controlling the particle size distribution of the neutralizer and the fiber cross-sectional shape during polymerization, using neutralizers with particle sizes ranging from 10-150 microns and solution concentrations within a specific range, the spinning process parameters, including the curing and tensile processes of the spinning liquid, are optimized to stabilize the breaking strength and elongation of the fibers.

Benefits of technology

The standard deviation of the breaking strength and elongation of the fiber is less than 0.5cN/dtex and 7%, ensuring the stable tear strength of the fabric, and is suitable for protective clothing such as fire garments and heat-resistant work clothes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025019362000001
    Figure 2025019362000001
  • Figure 2025019362000002
    Figure 2025019362000002
Patent Text Reader

Abstract

To obtain a heat-resistant flame-retardant working wear having stable fabric physical properties (especially, tear strength) using a meta-type all aromatic polyamide fiber having a standard deviation of a breaking strength of the fiber of 0.5cN / dtex or under and a standard deviation of a breaking elongation of the fiber of 7% or under as a fabric.SOLUTION: On manufacturing a meta-type all aromatic polyamide fiber by spinning a spinning dope containing meta-type all aromatic polyamide into a coagulation bath, followed by solidifying, a neutralizer used for neutralization of the spinning dope of the meta-type all aromatic polyamide is a neutralizer having a particle size (D90) of 90% or under of the whole particle amount of over 10 μm and less than 150 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a meta-type wholly aromatic polyamide fiber and a production method thereof, and more specifically, to a meta-type wholly aromatic polyamide fiber in which the standard deviations of breaking strength and breaking elongation, and the fiber cross-sectional shape are controlled within specific ranges, and a production method thereof. [Background technology]

[0002] Conventionally, among fully aromatic polyamides, meta-type fully aromatic polyamide (hereinafter, sometimes referred to as "meta-aramid") fibers, represented by polymetaphenylene isophthalamide, have been particularly useful as heat-resistant and flame-retardant fibers, and have been used in fields where these properties are exhibited, such as industrial applications such as filters and electronic components, and disaster prevention and safety clothing applications such as protective clothing, where heat resistance, flame retardancy, and flame resistance are important (see Patent Documents 1 to 5).

[0003] It is also well known that these meta-type wholly aromatic polyamides are soluble in amide-based polar solvents, and can be made into fibers from a polymer solution in which the meta-type wholly aromatic polyamide is dissolved in the solvent by methods such as dry spinning, wet spinning, and semi-dry / semi-wet spinning.

[0004] Until now, inorganic alkalis have been used in the polymerization process of meta-aramid fibers, but by using fine particles with a particle diameter of 10 μm or less, the problems of fuzz generation due to thread breakage on the nozzle surface and thread breakage during drawing have been improved (see, for example, Patent Document 6).

[0005] However, when inorganic alkali particles are dispersed in a solvent, they settle out, and when a dispersion of inorganic alkali that has settled out is used, it takes a long time for neutralization, which is unsuitable for industrial production.

[0006] Furthermore, particularly when meta-type wholly aromatic polyamide fibers are used in protective clothing, etc., visibility and distinctiveness are necessary, and furthermore, decorativeness and design are also important elements of the product, and a variety of processing steps are performed, so stabilizing the tear strength of fabrics containing meta-type wholly aromatic polyamide fibers has become an important technical challenge. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2007 / 089008 [Patent Document 2] JP 2010-084237 A [Patent Document 3] International Publication No. 2011 / 118022 [Patent Document 4] JP 2011-236543 A [Patent Document 5] JP 2020-020057 A [Patent Document 6] Japanese Patent Application Publication No. 57-067631 Summary of the Invention [Problem to be solved by the invention]

[0008] As a result of intensive research to solve the above problems, the present inventors have found that the reason why the tear strength of a fabric containing a meta-type wholly aromatic polyamide fiber is unstable is that the breaking strength and elongation of the meta-type wholly aromatic polyamide fiber vary greatly within a lot and between lots. [Means for solving the problem]

[0009] Thus, an object of the present invention is to find a method for reducing the variation in the breaking strength and elongation of meta-type wholly aromatic polyamide fibers. As a result of intensive research, the present inventors have found that when the particle size distribution of the neutralizing agent used in the polymerization process of meta-type wholly aromatic polyamide fibers and the cross-sectional shape of the spun meta-type wholly aromatic polyamide fibers are controlled within specific ranges, the variation in the breaking strength and elongation of the meta-type wholly aromatic polyamide fibers can be reduced, thereby making it possible to further stabilize the tear strength of the fabric.

[0010] That is, according to the present invention, 1. A meta-type wholly aromatic polyamide fiber comprising a meta-type wholly aromatic polyamide as a constituent component, the fiber having a standard deviation of breaking strength of 0.5 cN / dtex or less, a standard deviation of breaking elongation of 7% or less, and a cross-sectional shape in which the ratio D2 / D1 of the major axis D2 to the minor axis D1 in the fiber cross section is less than 1.6; 2. A method for producing meta-type wholly aromatic polyamide fibers, comprising the steps of: spinning a spinning dope containing a meta-type wholly aromatic polyamide in a coagulation bath and solidifying the dope to produce a meta-type wholly aromatic polyamide fiber; neutralizing the meta-type wholly aromatic polyamide spinning dope by using a neutralizing agent having a particle diameter (D90) of 90% or less of the total particle amount exceeding 10 μm and less than 150 μm; 3. The method for producing a meta-type wholly aromatic polyamide fiber according to the above item 2, wherein the neutralizing agent is calcium hydroxide. 4. The method for producing a meta-type wholly aromatic polyamide fiber according to the above item 2, wherein a dope having a turbidity of 6.0 or less is used as a dope for spinning a meta-type wholly aromatic polyamide. And, 5. The method for producing a meta-type wholly aromatic polyamide fiber according to the above item 2, wherein a meta-type wholly aromatic polyamide having an IV of 3.0 (dL / g) or less and a dope having a dope viscosity of 800 (poise) or less is used as a dope for spinning a meta-type wholly aromatic polyamide. is provided. Effect of the Invention

[0011] According to the present invention, meta-type wholly aromatic polyamide fibers having a standard deviation of fiber breaking strength of 0.5 cN / dtex or less and a standard deviation of fiber breaking elongation of 7% or less can be obtained, and protective clothing produced using the meta-type wholly aromatic polyamide fibers is heat-resistant, flame-retardant work clothing with stable fabric properties (especially tear strength), which makes it suitable for use as protective clothing such as firefighting clothing and heat-resistant work clothing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. The meta-type wholly aromatic polyamide in the present invention is a wholly aromatic polyamide produced by, for example, solution polymerization or interfacial polymerization using a meta-type aromatic diamine and a meta-type aromatic dicarboxylic acid halide as raw materials, but may also be a wholly aromatic polyamide copolymerized with other copolymerization components such as a para-type wholly aromatic polyamide within a range that does not impair the object of the present invention.

[0013] Examples of the meta-type wholly aromatic diamine that can be used include metaphenylenediamine, 3,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl sulfone, and derivatives thereof having a substituent such as halogen or an alkyl group having 1 to 3 carbon atoms on the aromatic ring, such as 2,4-toluylenediamine, 2,6-toluylenediamine, 2,4-diaminochlorobenzene, 2,6-diaminochlorobenzene, etc. Among these, metaphenylenediamine or the above mixed diamine containing 70 mol % or more of metaphenylenediamine is preferred.

[0014] As the meta-type aromatic dicarboxylic acid halide, isophthalic acid halides such as isophthalic acid chloride and isophthalic acid bromide, and derivatives thereof having a substituent such as halogen or an alkoxy group having 1 to 3 carbon atoms on the aromatic ring, for example, 3-chloroisophthalic acid chloride and 3-methoxyisophthalic acid chloride, can be used. Among them, isophthalic acid chloride or the above mixed carboxylic acid halide containing 70 mol % or more of isophthalic acid chloride is preferred.

[0015] Examples of copolymerization components that can be used other than the above diamines and dicarboxylic acid halides include, as aromatic diamines, paraphenylenediamine, 2,5-diaminochlorobenzene, 2,5-diaminobromobenzene, benzene derivatives such as aminoanisidine, 1,5-naphthylenediamine, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ketone, 4,4'-diaminodiphenylamine, 4,4'-diaminodiphenylmethane, and the like; and, as aromatic dicarboxylic acid halides, terephthalic acid chloride, 1,4-naphthalenedicarboxylic acid chloride, 2,6-naphthalenedicarboxylic acid chloride, 4,4'-biphenyldicarboxylic acid chloride, 4,4'-diphenyletherdicarboxylic acid chloride, and the like.

[0016] The copolymerization ratio of these copolymerization components is preferably 20 mol % or less based on the total acid components of the polyamide, since if it is too high, the properties of the meta-type wholly aromatic polyamide tend to deteriorate. Particularly suitable meta-type wholly aromatic polyamides are polyamides in which 80 mol % or more of the total repeating units are composed of metaphenylene isophthalamide units, and among these, polymetaphenylene isophthalamide is preferred.

[0017] Next, since hydrochloric acid is generated as a by-product in the spinning dope of meta-type wholly aromatic polyamide after polymerization using the above raw materials, it is necessary to neutralize it with an inorganic alkali. As the neutralizing agent, calcium oxide, calcium hydroxide, calcium carbonate, lithium hydroxide, lithium carbonate, magnesium hydroxide, magnesium carbonate, etc. can be used, and among them, calcium hydroxide is preferable.

[0018] The neutralizer must have a particle size (D90) of 90% or less of the total particle amount exceeding 10 μm and less than 150 μm. If the D90 is smaller than 10 μm, precipitation occurs when mixed with the solvent, and the solvent does not become homogeneous, so that the neutralization cannot be stabilized and abnormal neutralization may occur. On the other hand, if the D90 is 150 μm or more, the viscosity increases when mixed with the solvent, and it is difficult to mix with the dope, making it difficult to use as a neutralizer.

[0019] When calcium carbonate is used as the neutralizing agent, the raw material is limestone, which undergoes processes such as crushing, calcination, and hydration (slaked) to change its name to calcium carbonate, quicklime, or slaked lime, and its method of use also changes.

[0020] Hydrated lime is made by adding water to quicklime and slaked and ripening it. The particle size of this hydrated lime can be determined by the crushing and classification process. However, as expressed by the average particle size, it is impossible to make all the particles the same size.

[0021] Next, the meta-type wholly aromatic polyamide obtained by the above method is dissolved in a solvent to prepare a spinning dope, but it is also possible to use the meta-type wholly aromatic polyamide as it is without isolating it after polymerization as a spinning dope. An amide-based solvent can generally be used as the solvent here, and examples of main amide-based solvents include N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), and N,N-dimethylacetamide (DMAc). Among these, it is preferable to use NMP or DMAc from the viewpoints of solubility and handling safety.

[0022] The solution concentration may be appropriately selected from the viewpoints of the coagulation rate in the subsequent spinning / coagulation process and the solubility of the polymer. For example, when the polymer is polymetaphenylene isophthalamide and the solvent is NMP, it is usually preferable to set the concentration in the range of 10 to 30 mass %.

[0023] The turbidity of the spinning dope thus obtained is preferably 6.0 or less, and more preferably 3.5 to 1.5. If the turbidity exceeds 6.0, coagulation may be insufficient, and the target fiber strength and elongation may not be obtained.

[0024] The spinning dope preferably uses a meta-type wholly aromatic polyamide having an intrinsic viscosity IV of 3.0 (dL / g) or less. More preferably, it is 2.5 to 2.0 (dL / g) or less. The dope viscosity is preferably 800 (poise) or less. More preferably, it is 750 to 500 (poise) or less. If the IV exceeds 3.0 (dL / g), the viscosity becomes high, which may adversely affect the spinnability. On the other hand, if the dope viscosity exceeds 800 (poise), the viscosity becomes too high, which may make it impossible to spin the dope.

[0025] Next, the spinning dope prepared by the above method is spun into a coagulation liquid and coagulated. The spinning device used in this case is not particularly limited, and a conventionally known wet spinning device can be used. In addition, as long as it can perform stable wet spinning, there is no need to particularly limit the number of spinning holes, arrangement state, hole shape, etc. of the spinneret, and for example, a multi-hole spinneret for staple fibers having 500 to 30,000 holes and a spinning hole diameter of 0.05 to 0.2 mm may be used.

[0026] In the present application, in order to make the ratio D2 / D1 of the major axis D2 to the minor axis D1 in the fiber cross section less than 1.6, the coagulation speed of the spinning dope during coagulation can be slowed down to suppress the formation of a skin during coagulation and reduce the ratio D2 / D1. In addition, in order to slow down the coagulation speed of the spinning dope during coagulation, for example, a method of lowering the concentration of an amide-based solvent in the coagulation bath described below can be exemplified. The temperature of the spinning dope when it is spun from the spinneret is suitably in the range of 10 to 90°C.

[0027] As an example of the coagulation bath used to obtain the fiber of the present invention, an aqueous solution of an amide-based solvent not containing inorganic salts with a concentration of 45 to 60% by mass is used at a bath temperature in the range of 10 to 35°C. If the concentration of the amide-based solvent is less than 45% by mass, the skin layer will be thick, the washing efficiency in the washing step will decrease, the D2 / D1 of the final fiber will exceed 1.6, or the solvent will remain in the fiber. If the concentration of the amide-based solvent exceeds 60% by mass, uniform coagulation cannot be performed even in the fiber interior, and therefore, many problems such as breakage of the single yarn during fiber processing will occur. The appropriate immersion time of the fiber in the coagulation bath is in the range of 0.1 to 30 seconds.

[0028] Next, while the fibers obtained by coagulation in the coagulation bath are in a plastic state, the fibers are stretched in a plastic stretching bath. The plastic stretching bath liquid is not particularly limited, and any conventionally known bath liquid can be used.

[0029] In order to obtain the fiber of the present invention, the draw ratio in the plastic drawing bath is preferably in the range of 3.5 to 5.0, more preferably in the range of 3.7 to 4.5. In the production of the fiber of the present invention, the removal of the solvent from the coagulated yarn can be promoted by plastic drawing in a specific range of draw ratio in the plastic drawing bath.

[0030] If the stretching ratio in the plastic stretching bath is less than 3.5 times, the solvent may not be sufficiently removed from the coagulated yarn. In addition, the breaking strength may be insufficient, which may make it difficult to handle in processing steps such as spinning. On the other hand, if the stretching ratio exceeds 5.0 times, single yarn breakage may occur, which may result in poor process stability. The temperature of the plastic stretching bath is preferably in the range of 10 to 90°C. A temperature in the range of 20 to 90°C is preferable to provide good process stability.

[0031] Next, the solvent remaining in the fiber is washed away. In this step, the fiber stretched in the plastic stretching bath is thoroughly washed. Since washing affects the quality of the resulting fiber, it is preferable to perform washing in multiple stages.

[0032] In particular, the temperature of the washing bath in the washing step and the concentration of the amide-based solvent in the washing bath liquid affect the state of extraction of the amide-based solvent from the fiber and the state of penetration of water from the washing bath into the fiber. Therefore, from the viewpoint of optimizing these, it is preferable to perform the washing step in multiple stages and control the temperature conditions and the concentration conditions of the amide-based solvent. The temperature conditions of the washing and the concentration conditions of the amide-based solvent are not particularly limited as long as they satisfy the quality of the finally obtained fiber. However, if the first washing bath is at a high temperature of 60°C or more, water will penetrate into the fiber all at once, generating huge voids in the fiber and causing deterioration of quality. For this reason, it is preferable to set the first washing bath at a low temperature of 30°C or less.

[0033] If the solvent remains in the fiber, it not only reduces the flame retardancy of the fiber, but also is undesirable in terms of environmental safety in processing products using the fiber and in using products formed using the fiber. Therefore, the amount of solvent contained in the fiber used in the present invention is preferably 0.2 mass% or less, more preferably 0.15 mass% or less, and particularly preferably 0.1 mass% or less.

[0034] Next, in the dry heat treatment step, the fiber that has been through the washing step is dried and heat treated. The method of the dry heat treatment is not particularly limited, but examples thereof include a method using a hot roller, a hot plate, etc. By passing through the dry heat treatment, the meta-type wholly aromatic polyamide fiber used in the present invention can finally be obtained.

[0035] In order to obtain the meta-type wholly aromatic polyamide fiber of the present invention, it is preferable to perform a dry heat treatment at 100°C for drying, and then repeat dry heat treatment at least twice or more for 5 seconds or less each time at a temperature range of 280 to 310°C, and more preferably at a temperature range of 290 to 300°C. If the heat treatment temperature is less than 280°C, the crystallization of the fiber may be insufficient, and the shrinkage of the fiber may increase. The dry heat treatment performed at a temperature range of 280 to 310°C contributes to improving the breaking strength of the obtained fiber.

[0036] The meta-type wholly aromatic polyamide fiber that has been subjected to the dry heat treatment may be further subjected to a crimping process, if necessary. After the crimping process, the fiber may be cut to an appropriate fiber length and provided to the next process. In some cases, the fiber may be wound up as a multifilament yarn.

[0037] The meta-type wholly aromatic polyamide fiber of the present invention thus obtained has meta-type wholly aromatic polyamide as its main (or may be said to contain) constituent component, and it is necessary that the standard deviation of the breaking strength of the fiber is 0.5 cN / dtex or less, and the standard deviation of the breaking elongation of the fiber is 7% or less.

[0038] If the standard deviation of the breaking strength of the fiber exceeds 0.5 cN / dtex, the tear strength of the fabric will be lower than the target.The preferred value of the standard deviation of the breaking strength is 0.3 cN / dtex to 0.15 cN / dtex. In addition, if the standard deviation of the breaking elongation of the fiber exceeds 7%, the tear strength of the fabric, like the breaking strength, will be lower than the target. The preferred value of the standard deviation of the breaking elongation is 5% to 3%.

[0039] The meta-type wholly aromatic polyamide fiber of the present invention must have a cross-sectional shape in which the ratio D2 / D1 of the long diameter D2 to the short diameter D1 in the fiber cross section is less than 1.6. Here, the minor axis D1 and major axis D2 are values ​​measured by the method described below, and when D2 / D1 is 1.6 or more, the standard deviations of the breaking strength and elongation vary widely, and the tear strength of the fabric decreases. The preferred value of D2 / D1 is 1.2 to 1.4. EXAMPLES

[0040] The present invention will be described in more detail with reference to the following examples and comparative examples. However, these examples and comparative examples are provided to aid in the understanding of the present invention, and are not intended to limit the scope of the present invention. In addition, the physical properties in the examples were measured by the following methods.

[0041] <Fiber tensile strength and elongation> Based on JIS L1015, the tensile strength and tensile elongation of the fiber were determined by measuring the values ​​under the following conditions using an Instron Model 5565. (Measurement conditions) Grip distance: 20mm Initial load: 0.044cN(1 / 20g) / dtex Pulling speed: 20mm / min

[0042] <Standard deviation of fiber tensile strength and tensile elongation> Fifty samples were collected using the collection method described below, and the tensile strength and tensile elongation of the fibers were measured using the methods described above, and the standard deviation was calculated.

[0043]

number

[0044] To find standard deviation, 1. find the average, 2. find the deviation (number - average), 3. find the variance (mean squared deviation), 4. calculate the positive square root of the variance.

[0045] <Sample collection method for measuring standard deviation of fiber tensile strength and tensile elongation> The standard deviation is calculated from 50 samples (single yarn) extracted under the same conditions or environment. The same conditions or environment may be, for example, 50 randomly selected fiber samples from the same production (one package), or 50 randomly selected filament samples from the same production, or 50 randomly selected fiber samples from different lots, or 50 samples of fibers randomly extracted from a sewn product obtained, or 50 samples of fibers randomly extracted from input and output spun yarns, or 50 samples of fibers randomly extracted from a fabric, etc.

[0046] <Ratio of major axis D2 to minor axis D1 (D2 / D1)> The ratio D2 / D1 of the major axis D2 of the cross section of the meta-type wholly aromatic polyamide fiber to the minor axis D1 of the cross section perpendicular to the fiber axis direction of the meta-type wholly aromatic polyamide fiber is determined by measuring the actual dimensions from a micrograph of the cross section.

[0047] <D90 of inorganic alkali> Based on ISO13320, 0.1% by mass of inorganic alkali was mixed uniformly in 100% by mass of solvent (DMAc) using a MICROTRAC MT3000, and the particle size (D90) of particles with a specific particle size that accounted for 90% or less of the total and the particle size (D10) of particles with a specific particle size that accounted for 10% or less of the total were measured with the inorganic alkali dispersed.

[0048] <Intrinsic Viscosity (IV) of Meta-type Wholly Aromatic Polyamide> The intrinsic viscosity (IV) was measured using a Hydramotion XL series at 30°C in 97% concentrated sulfuric acid. (Measurement conditions) 10 ml of the dope to be measured is poured into a viscosity tube in 97% sulfuric acid at 30°C, and the time it takes for the dope to fall 10 cm inside the viscosity tube is measured, and IV is calculated using the following formula. IV = In(t / to) × 2 In: Natural logarithm (2.3log) t: sample drop time To: Blank fall time

[0049] <Dope Viscosity> The viscosity of the dope was measured using a B-type viscometer (DV-II+Pro model manufactured by EKO INSTRUMENTS CO., LTD.) under the following conditions. (Measurement conditions) Spindle: No.04 Spindle speed: 20 rpm

[0050] <Dope turbidity> Using a CENTRAL KAGAKU Co., Ltd. Model No. ST-100, the dope to be measured was placed in a quartz cell, and the measured value was taken as the dope turbidity.

[0051] <Method for measuring the amount of remaining solvent> Approximately 8.0 g of fiber is collected, dried at 105°C for 120 minutes, cooled in a desiccator, and the fiber mass (M1) is weighed. Next, the fiber is refluxed in methanol for 1.5 hours using a Soxhlet extractor to extract the amide-based solvent contained in the fiber. After extraction, the fiber is taken out and vacuum dried at 150°C for 60 minutes, cooled in a desiccator, and the fiber mass (M2) is weighed. The amount of solvent (amide-based solvent mass) N (%) remaining in the fiber is calculated using the obtained M1 and M2 according to the following formula. N(%)=[(M1-M2) / M1]×100

[0052] [Example 1] [Spinning solution preparation process] 721.5 parts by mass of N,N-dimethylacetamide (DMAc) with a moisture content of 100 ppm or less was weighed out in a reaction vessel under a dry nitrogen atmosphere, and 97.2 parts by mass (50.18 mol%) of metaphenylenediamine was dissolved in this DMAc and cooled to 0° C. 181.3 parts by mass (49.82 mol%) of isophthalic acid chloride (hereinafter abbreviated as IPC) was further gradually added to this cooled DMAc solution with stirring to carry out a polymerization reaction.

[0053] Next, 66.6 parts by mass of calcium hydroxide powder with a D90 of 47 μm was weighed and slowly added to the polymer solution after the polymerization reaction was completed to carry out a neutralization reaction. After the addition of calcium hydroxide was completed, the mixture was stirred for another 40 minutes to obtain a transparent polymer solution. Polymetaphenylene isophthalamide was isolated from the resulting polymer solution, and its intrinsic viscosity (IV) was measured and found to be 1.2. The polymer concentration in the polymer solution was 17% by mass. The polymer solution was depressurized and degassed to prepare a spinning solution (dope for spinning) having a dope turbidity of 2.2 and a dope viscosity of 605 (poise).

[0054] [Spinning and coagulation process] The spinning dope was discharged and spun from a spinneret having a circular cross section, a hole diameter of 0.07 mm, and 500 holes into a coagulation bath at a bath temperature of 30° C. The composition of the coagulation liquid was water / DMAc=45 / 55 (parts by mass), and the dope was discharged and spun into the coagulation bath at a yarn speed of 7 m / min.

[0055] [Plastic drawing bath drawing process] Subsequently, the film was stretched at a stretch ratio of 3.7 times in a plastic stretching bath having a composition of water / DMAc=45 / 55 at a temperature of 40° C.

[0056] [Cleaning process] After stretching, the film was washed in a 20°C water / DMAc=70 / 30 bath (immersion length 1.8 m), then in a 20°C water bath (immersion length 3.6 m), and further in a 60°C warm water bath (immersion length 5.4 m) for thorough washing.

[0057] [Dry heat treatment process] The washed fibers were subjected to a dry heat treatment using a hot roller having a surface temperature of 300° C. to obtain meta-type wholly aromatic polyamide fibers.

[0058] [Shrinkage and cutting process] The fibers obtained were crimped through a crimper and then cut into short fibers of 51 mm length with a cutter to obtain meta-type wholly aromatic polyamide fibers. The results of various measurements of the obtained fibers are shown in Table 1.

[0059] [Example 2] Except for using calcium hydroxide having a D90 of 34 μm (with less than 10% of particles having a diameter of 10 μm or less) in the spinning solution preparation step, the same procedure as in Example 1 was carried out to produce meta-type wholly aromatic polyamide fibers. The results of various measurements of the obtained fibers are shown in Table 1. In this case, the intrinsic viscosity (IV) of the polymetaphenylene isophthalamide was 1.1 dL / g, the dope turbidity was 3.1, and the dope viscosity was 680 (poise).

[0060] [Comparative Example 1] Except for using calcium hydroxide having a D90 of 5 μm in the spinning solution preparation step and changing the composition of the coagulation solution to water / DMAc=70 / 30 (parts by mass), the same procedure as in Example 1 was carried out to produce meta-type wholly aromatic polyamide fibers. The results of various measurements of the obtained fibers are shown in Table 1. In this case, the intrinsic viscosity (IV) of the polymetaphenylene isophthalamide was 1.8 dL / g, the dope turbidity was 3.2, and the dope viscosity was 500 (poise).

[0061] [Comparative Example 2] Except for using calcium hydroxide having a D90 of 150 μm in the spinning solution preparation step, the same procedure as in Example 1 was carried out to produce a meta-type wholly aromatic polyamide fiber. The results of various measurements of the obtained fiber are shown in Table 1. In this case, the intrinsic viscosity (IV) of the polymetaphenylene isophthalamide was 3.5 dL / g, the dope turbidity was 2.7, and the dope viscosity was 620 (poise).

[0062] [Comparative Example 3] A meta-type wholly aromatic polyamide fiber was produced in the same manner as in Example 1, except that in the spinning and coagulation steps, the composition of the coagulation liquid was water / DMAc=90 / 10 (parts by mass). The results of various measurements of the obtained fiber are shown in Table 1. In this case, the intrinsic viscosity (IV) of the polymetaphenylene isophthalamide was 1.2 dL / g, the dope turbidity was 2.2, and the dope viscosity was 605 (poise).

[0063] [Table 1] [Industrial Applicability]

[0064] According to the present invention, meta-type wholly aromatic polyamide fibers having a standard deviation of fiber breaking strength of 0.5 cN / dtex or less and a standard deviation of fiber breaking elongation of 7% or less can be obtained, and protective clothing produced using the meta-type wholly aromatic polyamide fibers is heat-resistant, flame-retardant work clothing with stable fabric properties (especially tear strength). Therefore, it can be suitably used as protective clothing such as firefighting clothing and heat-resistant work clothing. For these reasons, the fiber of the present invention has high industrial applicability and is extremely valuable in industry.

Claims

1. A meta-type wholly aromatic polyamide fiber, comprising a meta-type wholly aromatic polyamide as a constituent component, characterized in that the standard deviation of the breaking strength of the fiber is 0.5 cN / dtex or less, the standard deviation of the breaking elongation of the fiber is 7% or less, and the cross-sectional shape of the fiber has a ratio D2 / D1 of the major axis D2 to the minor axis D1 in the fiber cross section of less than 1.

6.

2. A method for producing meta-type wholly aromatic polyamide fibers, comprising the steps of: spinning a spinning dope containing a meta-type wholly aromatic polyamide in a coagulation bath and solidifying the dope to produce meta-type wholly aromatic polyamide fibers; neutralizing the meta-type wholly aromatic polyamide spinning dope by using a neutralizing agent having a particle diameter (D90) of 90% or less of the total particle amount exceeding 10 μm and less than 150 μm.

3. 3. The method for producing meta-type wholly aromatic polyamide fibers according to claim 2, wherein the neutralizing agent is calcium hydroxide.

4. 3. The method for producing meta-type wholly aromatic polyamide fibers according to claim 2, wherein a dope having a turbidity of 6.0 or less is used as the meta-type wholly aromatic polyamide spinning dope.

5. 3. A method for producing a meta-type wholly aromatic polyamide fiber according to claim 2, wherein a meta-type wholly aromatic polyamide having an IV of 3.0 (dL / g) or less and a dope having a dope viscosity of 800 (poise) or less is used as a dope for spinning a meta-type wholly aromatic polyamide.

Citation Information

Patent Citations

  • Preparation of aromatic polyamide solution

    JP1982067631A

  • Easily dyeable meta-form wholly aromatic polyamide fiber

    JP2010084237A

  • Meta-type wholly aromatic polyamide fiber

    JP2011236543A

  • Flame-retardant fabric comprising spun-dyed meta-type wholly aromatic polyamide fiber, and laminated protective clothing made of the fabric

    JP2020020057A

  • Meta-type fully aromatic polyamide fiber having excellent high-temperature processability and method for production thereof

    WO2007089008A1